Desenvolvimento de um protocolo com a utilização da toxina botulínica tipo A associada a luteolina no controle dos sintomas relacionados à rosácea - Malachoski, Karla Glazielle Gonçalves dos Santos (2021)
Rosacea is considered a lesion of the skin tissue with the presence of inflammatory infiltrate and depending on the degree presented it also presents a bacterial infiltrate, where it is possible to observe pustules in the affected regions. Despite affecting both sexes, rosacea is predominant in females, generally in women of lower phototypes and with respect to age, the prevalence is higher after 35 years of age. Most of the affected people suffer from the signs that the alteration presents because there is still no cure for such dysfunction, only control and which can often generate major disorders due to aggression to the organism. The treatments found that are most used today are basically divided into 2 classes of drugs - antibiotics and corticosteroids, both promote high side effects and, in some cases, concomitant use can trigger resistance as is the case with the antibiotic. Botulinum toxin is also used in isolation to try to control rosacea symptoms, but there is a need for new protocols that are more effective and longlasting with regard to the signs that rosacea presents. The main objective of this dissertation is to develop a protocol for the control of rosacea symptoms with the use of botulinum toxin A in association with anti-inflammatory drugs, in this case, luteolin. The protocol consists of hyperdiluting the botulinum toxin A, with 4 ml and adding 2 ml during the dilution of luteolin, having at the end a solution (serum + botulinum toxin A + Luteolin) of 6 ml, the application will be performed intradermally in all the affected regions, each point will be infiltrated from 1 to 2 units of the solution. The results were significant in controlling the signs and symptoms of rosacea and the average durability was 90 days, being then superior to the existing protocol, which is only the application of type A botulinum toxin.